Comparison of angiogenic potential between prevascular and non‐prevascular layered adipose‐derived stem cell‐sheets in early post‐transplanted period. Issue 2 (14th May 2013) - Sasagawa, Tadashi; Shimizu, Tatsuya; Sekiya, Sachiko; Yamato, Masayuki; Okano, Teruo
Abstract Layered adipose‐derived stem cell (ADSC) sheet transplantation is attracting attention as a new stem cell therapeutic strategy for damaged hearts. To prolong the function of tissue‐engineered constructs after transplantation, a rapid and sufficient vascularization of engrafted tissue is essential. The in vitro formation of network structures derived from endothelial cells (ECs) in grafts before transplantation contributes to the induction of functional anastomosis in vivo. This study compared the angiogenic potential of ADSC sheets containing dissociated ECs (non‐prevascular cell‐sheets) and networked ECs (prevascular cell‐sheets) after transplantation. For preparing the two different types of ECs‐containing layered cell‐sheets, human umbilical vein endothelial cells (HUVECs) were sandwiched between two human ADSC sheets. Non‐prevascular cell‐sheets were obtained immediately after sandwiching without further cultivation. Prevascular cell‐sheets were harvested form temperature‐responsive culture dishes following re‐cultivation for allowing them to form an EC network structure. In transplant experiments in the subcutaneous tissues of immune‐deficient rat for 4 days, prevascular cell‐sheets were observed to promote neovascularization with HUVEC‐lined microvessels. In contrast, neovessels were hardly observed in non‐prevascular cell‐sheets. These results suggested that prefabricated EC network in layered cell‐sheet was effective for making a rapid connection to the host vasculature in the early post‐transplanted period. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 358–365, 2014.